THE INFLUENCE OF CONTENT MARKETING, OMNICHANNEL MARKETING, AND ELECTRONIC WORD OF MOUTH ON PURCHASE DECISIONS THROUGH BRAND AWARENESS IN THE BCA ‘DON’T KNOW KASIH NO.’ ADVERTISEMENT - Syahdan Muhamad Rezky; Putu Nina Madiawati; Mahir Pradana (PT. Jurnal Center Indonesia Publisher, 2026)
Digital transformation has reshaped the marketing communication paradigm of the banking industry in Indonesia, encouraging financial institutions to adopt creative strategies to reach digital consumers. This study aims to analyze the influence of content marketing, omnichannel marketing, and electronic word of mouth (eWOM) on purchase decisions through brand awareness in BCA’s public service advertisement “Don’t Know Kasih No!”. This banking security education campaign successfully garnered more than 100 million views through its unique storytelling approach, engaging audiovisual elements, and relevant humor, making it an interesting phenomenon to be examined scientifically. This research employs a descriptive quantitative method using the Structural Equation Modeling–Partial Least Square (SEM-PLS) approach. The research population consists of Indonesian individuals aged 17–40 years (Generation Z and Millennials) who are BCA customers and have been exposed to the “Don’t Know Kasih No.!” advertisement. The sample size was determined using Cochran’s formula, resulting in a minimum of 100 respondents, selected through purposive sampling. Data were collected using an online questionnaire developed based on a five-point Likert scale containing 47 statement items. Data analysis was conducted using SmartPLS 4.0 to evaluate validity, reliability, and structural hypothesis testing.